Training Non-Professional Interpreters and Translators in Public Services: DIALOGOS - Pena Díaz, Carmen (Estudios de Traducción, 2026)
The growing diversity of migrant populations in Europe has heightened the demand for communication across languages of lesser diffusion (LLD). While professional translators and interpreters exist for majority languages, gaps remain for communities speaking recently arrived or low-resource languages. In these cases, non-professional interpreters and translators (NPITs)—often bilingual or heritage speakers with little or no formal training—frequently bridge communication in healthcare, legal, and humanitarian settings. The Erasmus+ DIALOGOS project sought to address this situation by mapping LLDs in Spain, Italy, and Greece, identifying communication needs, and developing a training module for NPITs. This article presents the rationale, methodology, results, and reflections from the project. The study combined surveys and interviews with stakeholders, an analysis of existing resources, and a pilot training course. Findings reveal significant reliance on NPITs in public service settings, major training gaps, and the need to balance urgent communication demands with ethical and professional standards. The pilot course confirmed the feasibility of training NPITs in essential interpreting and translation skills, though challenges remain in scaling up training and ensuring professional recognition. The article situates these findings in the broader scholarship on NPIT, crisis translation, and public service interpreting, highlighting the risks, opportunities, and directions for future work.